RETRACTED ARTICLE: Engaging in Short-Term Moderate-Intensity Exercise Increases Growth Hormone Levels in Individuals with Obesity - Muhammad; Siantoro, Gigih; Subagio, Irmantara; Yosika, Ghana Firsta; Phanpheng, Yanyong; Pramono, Bayu Agung; Kusuma, I Dewa Made Aryananda Wijaya; Pranoto, Adi (Physical Education Theory and Methodology, 2024)
Objectives. This study aimed to analyze the effect of a four-week moderate-intensity exercise regimen on increasing growth hormone (GH) levels in individuals with obesity. Materials and methods. A total of 25 female individuals aged 20-25 years, with a body mass index (BMI) of 27.50-37.00 kg/m², were involved in the study and randomly divided into two groups, namely the control group (CON; n = 12) and the moderate-intensity exercise group (MIE; n = 13). The moderate-intensity exercise regimen (treadmill exercise for 30 minutes at 60-70% of HRmax, and resistance exercise for 30 minutes at 60-70% of 1RM) was conducted 3 times per week for a period of 4 weeks. Blood samples from participants were collected pre- and post-exercise sessions, and GH levels were analyzed using the Enzyme-Linked Immunosorbent Assay method. Data analysis techniques used the paired sample t-test with a significance level of 5 %. Results. The paired sample t-test results of GH levels between the pre-exercise and post-exercise sessions in the CON group showed a change from (1291.79 ± 383.76 to 1151.53 ± 484.80 pg/mL; p = 0.694), while the MIE group demonstrated the following dynamics of change — from (1161.79 ± 133.72 to 2103.83 ± 357.09 pg/mL; p = 0.006). Conclusions. The main findings of this study revealed that after implementing a four-week moderate-intensity exercise intervention, a significant increase in GH levels was observed in obese females.